2012
DOI: 10.1093/annonc/mdr441
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and pegylated liposomal doxorubicin versus carboplatin and paclitaxel in partially platinum-sensitive ovarian cancer patients: results from a subset analysis of the CALYPSO phase III trial

Abstract: Carboplatin-PLD has a more favorable risk-benefit profile than CP in patients with partially platinum-sensitive ROC and should be considered an effective treatment option for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
0
56
1
2
Order By: Relevance
“…Accompanying publications were identified that present results on mature OS data, 56 clinical effectiveness results in the subgroup of patients with PPS ovarian cancer (relapse at between 6 and 12 months since receipt of last cycle of chemotherapy) 57 and QoL. 59 The trial was of a non-inferiority design with the aim of determining whether PLDH (30 mg/m 2 ) plus carboplatin (AUC 5) every 4 weeks was non-inferior to the standard treatment of paclitaxel (175 mg/m 2 ) plus carboplatin every 3 weeks.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying publications were identified that present results on mature OS data, 56 clinical effectiveness results in the subgroup of patients with PPS ovarian cancer (relapse at between 6 and 12 months since receipt of last cycle of chemotherapy) 57 and QoL. 59 The trial was of a non-inferiority design with the aim of determining whether PLDH (30 mg/m 2 ) plus carboplatin (AUC 5) every 4 weeks was non-inferior to the standard treatment of paclitaxel (175 mg/m 2 ) plus carboplatin every 3 weeks.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…31 reported an analysis of PFS in the subgroup of patients with PPS ovarian cancer. 57 The PPS subgroup comprised 161 patients in the PLDH plus carboplatin group and 183 patients in the paclitaxel plus carboplatin group. Baseline characteristics were similar in the two treatment groups.…”
Section: Fully Platinum Sensitivementioning
confidence: 99%
“…The recent CALYPSO trial demonstrated the efficacy of PLD/carboplatin combination treatments for recurrent platinum-sensitive disease. This combination is currently associated with a more favorable risk-benefit profile than paclitaxel/carboplatin in patients with partially platinumsensitive recurrent ovarian carcinoma (14). A previous study in elderly patients revealed that PLD demonstrated an improved therapeutic index with less toxicity than paclitaxel/carboplatin (15).…”
Section: Discussionmentioning
confidence: 99%
“…10 In particular, carboplatin/pegylated liposomal doxorubicin (PLD) combination is considered in the clinical practice an alternative choice compared with carboplatin/paclitaxel in this specific setting. [11][12][13][14] Patients with a PFI of 6-12 mo are defined platinumpartially-sensitive and showed an intermediate likelihood of responding to a platinum-based regimen. 14 In this subgroup it has been recently hypothesized, based on preclinical and clinical findings, a potential benefit derived from an "artificial" prolongation of the PFI by the use of a platinum-free regimen (such as trabectedine-PLD combination).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Patients with a PFI of 6-12 mo are defined platinumpartially-sensitive and showed an intermediate likelihood of responding to a platinum-based regimen. 14 In this subgroup it has been recently hypothesized, based on preclinical and clinical findings, a potential benefit derived from an "artificial" prolongation of the PFI by the use of a platinum-free regimen (such as trabectedine-PLD combination). [15][16][17] These trials reported significant advantage in progression free survival (PFS) which did not translate in overall survival (OS) prolongation.…”
Section: Introductionmentioning
confidence: 99%